Targeted Economic Development: Its Role in Maine Economic Policy - Dickstein, Carla (Maine Policy Review, 1996)
Targeted economic development strategies challenge traditional approaches to economic development by making explicit the recipients of job growth and job creation. They link economic development concerns such as business growth and a positive business climate to often-ignored social criteria that are reflected in the question of who wins and who loses in our present economy. Carla Dickstein brings a practitioner’s perspective to this issue by relating Coastal Enterprises Inc.’s experience in using gap financing programs to link people with low incomes to jobs created through business start-ups or expansions.
Keywords: Maine; economic development; welfare to work; employment training